Relation between Class I malocclusion and bad oral habits in children with autism in Makassar: Hubungan maloklusi Klas I dengan kebiasaan buruk oral pada anak dengan autisme di Makassar - Muh. Chaerul Gunawan; Muh. Harun Achmad; Marhamah; Yayah Inayah (Makassar Dental Journal, 2024)
Poor oral habits are more common in individuals with autism. There is a greater prevalence of bruxism, mouth breathing, biting objects, lips or tongue, nail biting, and finger sucking. Childhood autism patients showed a significant increase in the prevalence of severe crowding, posterior crossbite, and increased overjet in the autism group. This article examines the determinants of Dewey's modified Class I malocclusion classification and poor oral habits in childhood autism. The study was quantitative with descriptive observational method. A high rate of Angle class I malocclusion was found in patients with autism. A total of 68.6% of children with autism had Angle class I malocclusion and 60% of children with autism had poor oral habits. It was concluded that the incidence of Angle class I malocclusion and poor oral habits in children with autism is very high.